Multilingual code switching in Algerian rap song lyrics : a functional approach - Metrouh, Farid; Mebtouche, Fatma Zohra Nedjai (Penerbit Universiti Kebangsaan Malaysia, 2022)
The use of multilingual lyrics in contemporary rap songs is a recurrent phenomenon in Algeria. If the lyrics are articulated through Algerian Arabic as a “base language,” the rappers saturate them with other languages for the sake of producing linguistically mixed songs. The most frequently used languages for code-switching are Standard Arabic, Berber (Tamazight), French, English and Spanish. These multilingual songs are most often embedded with code-switching (CS) where each used language assumes a particular discourse and pragmatic function. Therefore, this investigation aims to explore the recent phenomenon of multilingual CS in Algerian rap songs, basically to identify the functions that CS fulfils in song lyrics. Indeed, the analysis is mainly qualitative. A corpus of 10 songs from five Algerian rappers was collected and analysed. The researchers applied Gumperz's (1982) and Appel and Muysken’s (2005) functions of CS. This research answers the following question: What are the functions of CS in the lyrics of contemporary Algerian rap songs? The corpus included lyrics from rap songs produced in the period extending from 2019 to 2021. The findings reveal that the concerned multilingual CS is underpinned by a strategic positioning issued by rappers based on the social representations that specify each language in the Algerian sociolinguistic space concerning particular functions and socio-cultural considerations. A distinct set of functions was identified: 1) code-switching for language convenience, 2) identifying or drawing the attention of addressees, 3) serving as a marker of social/cultural identity, 4) complying with social norms, and 5) facilitating rhyme. This study can act as an asset for anyone who wants to extend the framework to examine multilingual CS in other Algerian communication contexts. Furthermore, it highlights the fundamental role of CS in rap song lyrics to increase the potential of promoting freedom of expression, multilingualism, and modernity.